Quality Characteristics Of Doughnuts From Pearl Millet Blended Composite Flours (Applied Biological Research, 2018)
This study was aimed to evaluate the quality of doughnuts made from pearl  millet-wheat-whey protein isolate composite blend. Flour blends of pearl millet  and refined wheat flour (RWF) were composite at replacement levels of 10, 20,  30 and 40% with 10% whey protein isolates in each treatment. The nutrient  contents of flour blends were determined using standard methods. The  products were analyzed for their proximate composition and sensory  attributes. The protein content of blends decreased steadily with increasing  content of pearl millet flour (PMF) (17.99% in 00:90:10::PMF:RWF:WPI to  14.44% in 40:50:10:: PMF:RWF:WPI) while crude fibre content increased.  The highest moisture content of 15.43%, crude fat 24.76%, crude fibre 2.36%  and ash content of 2.81% were observed in 40:50:10::PMF: RWF: WPI treatment. However, the treatment 00:90:10::PMF:RWF:WPI yielded highest  value of crude protein. On the basis of sensory evaluation, treatment  00:100:00::PMF:RWF:WPI recorded highest score for colour (8.96), texture  (8.74), taste (8.87) and overall acceptability (8.87) in doughnuts; whereas  reatment 40:50:10::PMF:RWF: WPI recorded lowest score for sensory  parameters. In general, incorporation of refined wheat flour and whey protein  isolates with pearl millet flour for doughnuts upto 20% level were acceptable.
Keywords: Doughnuts; pearl millet; proximate; refined sensory characteristics; wheat flour; whey protein isolates